2015
DOI: 10.1111/jcpe.12440
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of the influence of vertical incisions on the aesthetic outcome of the Miller class I and II recession treatment: a split‐mouth study

Abstract: MCAF with CTG and CAF with CTG allow obtaining satisfactory and comparable root coverage as well as an aesthetic outcome without the negative effect of vertical incisions on the appearance of soft tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…These speculations may explain the lower outcomes observed for teeth in the distal part of the flap, both in the eCAF and vCAF design, regardless adding a CTG. In line with our findings, a recent clinical trial found that vertical incisions did not affect clinical and esthetic outcomes of MAGRs treated with CAF + CTG . As suggested by Sanz and Simion, it may be concluded that although the choice of flap design depends on the GR depth, location, and number of teeth involved, avoiding vertical releasing incisions should be recommended to reduce the damage to the blood supply .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These speculations may explain the lower outcomes observed for teeth in the distal part of the flap, both in the eCAF and vCAF design, regardless adding a CTG. In line with our findings, a recent clinical trial found that vertical incisions did not affect clinical and esthetic outcomes of MAGRs treated with CAF + CTG . As suggested by Sanz and Simion, it may be concluded that although the choice of flap design depends on the GR depth, location, and number of teeth involved, avoiding vertical releasing incisions should be recommended to reduce the damage to the blood supply .…”
Section: Discussionsupporting
confidence: 89%
“…While performing two vertical releasing incisions can increase flap mobilization by 124.2% of its original length, in an angiographic study evaluating the tropism of flaps with different design, Mörman and Ciancio observed a reduced revascularization when verticals incisions were performed . The eCAF was introduced for the treatment of MAGRs to avoid the vertical incisions which may the impair vascular supply to the flap in its lateral part, and reduce the risk of keloid formation . However, the lack of vertical releasing incisions may pose a challenge in achieving a tension‐free flap, one of the main key factors in periodontal plastic surgery and in bone regeneration .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than coronally positioned flaps, flap designs used include tunnel technique [12,13], modified coronally advanced tunnel (MCAT) technique [26], modified coronally advanced flap (MCAF) technique by Zucchelli and De Sanctis [17,29], and a modified coronally positioned flap with a horizontal incision in the alveolar mucosa [20]. While most studies evaluated their outcome between 6 and 12 months postoperatively, 5-year results were reported by Zucchelli et al with mean root coverage of 97% [22].…”
Section: Root Coverage Procedures and Predictability Subepithelial Comentioning
confidence: 92%
“…Studies using subepithelial connective tissue graft (SCTG) on multiple Miller Class I and II gingival recession defects show mean percent root coverage ranging from 77 to 98%, with only 4 out of 17 studies reporting less than 90% [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Other than coronally positioned flaps, flap designs used include tunnel technique [12,13], modified coronally advanced tunnel (MCAT) technique [26], modified coronally advanced flap (MCAF) technique by Zucchelli and De Sanctis [17,29], and a modified coronally positioned flap with a horizontal incision in the alveolar mucosa [20].…”
Section: Root Coverage Procedures and Predictability Subepithelial Comentioning
confidence: 99%